The Rising Impact of Endometritis on Infertility in Cattle and Other Large Ruminants - Khan, Gul Zahra; Hanif, Nida; Kazmi, Syeda Umm E Farwa; Noor, Maaz; Ali, Muhammad; Awan, Ghulam Murtaza; Khalil Ur Rahman; Ahmed, Umair; Alam, Hafiz Munsif; Shahbaz, Muhammad (Indus Journal of Bioscience Research, 2025)
Endometritis is a significant cause of infertility in large ruminants, particularly in dairy cattle, leading to substantial economic losses in livestock farming. The condition, which is primarily caused by bacterial infections, retained placenta, and hormonal imbalances, disrupts reproductive health, resulting in prolonged calving intervals, reduced conception rates, and lower milk production. This review aims to provide a comprehensive synthesis of current knowledge on endometritis, exploring its epidemiology, pathophysiology, diagnosis, management strategies, and the impact on fertility. The review will also address emerging trends in the field, including molecular diagnostics, the role of the uterine microbiome, and the potential for vaccines and alternative therapies. Through a thorough analysis of the literature, the review identifies several key gaps in the understanding of endometritis, particularly regarding the molecular mechanisms behind bacterial infections and immune responses, as well as the broader microbial dynamics in the uterus. Furthermore, it highlights the need for more research on the economic impact of endometritis on herd productivity and sustainable management practices. The findings suggest that early diagnosis and timely intervention, along with improved farm management practices, such as better hygiene and nutrition, are essential for reducing the incidence of endometritis and improving fertility outcomes. It will also emphasize the role of precision livestock farming in the early detection and management of uterine infections. The review will conclude by recommending future research directions, including studies on the genetic and microbial factors contributing to susceptibility to endometritis, and exploring the development of alternative treatments that reduce reliance on antibiotics. These advancements are expected to contribute to more sustainable livestock farming practices and improved reproductive efficiency in large ruminants.